Causes of delay in construction projects: The case of oil and gas projects - Kazemi, Aliyeh; Katebi, Ali; Kazemi, Mohammad-Hossein (International Journal of Advanced Research in Engineering; Vol 4 No 1 (2018): International Journal of Advanced Research in Engineering, 2018)
Successful implementation of construction projects is one of the key factors for economic development of every country. Every year, a major part of the countries’ capital is allocated to civil and infrastructure projects, most of which are implemented with delay. Construction projects are often criticized for overrunning time and budgets. Analyzing the factors causing delay is essential with the aim of omitting them and timely implementation of these projects. Research to identify the reasons and causes of delays have been conducted in different countries and by various researches. In this paper, various research has studied different factors affecting construction projects delays have been studied. These factors have been identified in four groups consisted of owner, consultant, conductor, and other factors. Moreover, on account of the importance of oil and gas projects, the mentioned factors for these kinds of projects are taken into consideration. The results showed that change orders and changes in scope of work by owner, delay in reviewing of documents by consultant, inadequate experience and knowledge and errors during construction by contractor, and low productivity of laborer have been indicated as key factors comparing with the other as crucial factors causing delay in the oil and gas construction projects.